ENSO Influence on Western European Summer and Fall Temperatures. - Martija Díez, Maialen; Rodríguez de Fonseca, Belén; López Parages, Jorge (American Meteorological Society, 2021)
In certain regions, such as Europe, the increase in global air temperatures in the world is translated into more frequent extreme events. Recent studies suggest that the increasing intensity in heatwaves seems to be related to the interannual variability of the mean temperature, a finding that motivates the search for its possible predictability. El Niño–Southern Oscillation (ENSO) is the principal predictor of global climate variability at interannual time scales. Its impact on European climate has been deeply studied in relation to rainfall variability, but only a few studies exist that focus on its impact on temperature. In this work, we focus on the analysis of the interannual variability of maximum and minimum temperatures in order to find some predictability and trends. To that end, we choose the western European region, which has experienced intense heatwaves and is also the main region of air temperature interannual variability in Europe. Our results indicate that the ENSO impact on temperatures over this region is nonlinear and nonstationary. We have found the way in which, during the decades prior to 1980s, the increase in temperatures is related to La Niña in summer and to El Niño in fall during the decades after the 1980s, which shows a change in the seasonality of the impact. We study the dynamical mechanisms involved, which suggest a circumglobal response for summer and an arching-like teleconnection pattern in fall. The aforementioned warmer conditions in western European temperatures are found to be significantly correlated to ENSO characteristics of previous seasons, which suggests a potential source for improving the seasonal forecast.
https://v2.sherpa.ac.uk/id/publication/9932?template=romeo
Keywords: Meteorología; Cambios climáticos; Teleconnections; Climate variability; Sea surface temperature